Effect of liming on the mineral nutrition and yield of growing guava trees in a typic hapludox soil - Prado, Renato de Mello [UNESP]; Natale, William [UNESP] (Taylor & Francis Inc, 2008)
High soil acidity influences the availability of mineral nutrients and increases that of toxic aluminium (Al), which has a jeopardizing effect on plant growth. The objective of this research was to evaluate the effects of soil liming on the development of guava (Psidium guajava L.) plants, on soil chemical characteristics, and on fruit yield. The experiment was carried out at the Bebedouro Citrus Experimental Station, state of São Paulo, Brazil, in a Typic Hapludox soil, from August 1999 to March 2003. The treatments consisted of limestone dose: D0 = zero; D1 = half dose; D2 = total dose; D3 = 1.5 times the dose, and D4 = 2 times the dose to raise the V value to 70%. The doses corresponded to zero, 1.85, 3.71, 5.56, and 7.41tha(-1) applied to the upper soil layer (0-30cm deep) before planting. The results showed that liming caused an improvement in the evaluated soil chemical characteristics up to a depth of 60cm in soil samples both in the line and between lines. The highest fruit yields were obtained when the base saturation reached a value of 55% in the line and 62% between the lines. Foliar levels of calcium (Ca) and magnesium (Mg) were 8.8 and 2.5gkg-1, respectively. The highest limestone dose maintained the soil base saturation (at the layer of 0-20cm) in the line close to 55% during at least 40 months after the incorporation of limestone.
Keywords: fruit-bearing trees; limestone; Mineral nutrition; Psidium guajava; Soil acidity